The calibration of esophageal pressure by proper esophageal balloon filling volume: A clinical study - Jiang, Jing; Su, Longxiang; Cheng, Wei; Wang, Chunfu; Rui, Xi; Tang, Bo; Zhang, Hongmin; He, Huaiwu; Long, Yun (Frontiers in Medicine, 2022)
Background: Esophageal pressure (Pes) can be used as a reliable surrogate for pleural pressure, especially in critically ill patients requiring personalized mechanical ventilation strategies. How to choose the proper esophageal balloon filling volume and then find the optimal value of esophageal pressure remains a challenge. The study was to assess the feasibility of catheters for Pes monitoring in mechanically ventilated patients. Methods: Twelve patients under pressure controlled mechanical ventilation were included in this study. Raw esophageal pressure were recorded at different balloon filling volume. Then, the P-V curves were determined. VBEST was the filling volume providing the maximum difference between Pes at end-inspiration and end-expiration. The raw value of Pes was recorded, and the calibrated values of Pes were calculated by calculating the esophageal wall pressure (Pew) and esophageal elastance (Ees). Results: Twenty-four series of Pes measurements were performed. The mean VMIN and VMAX were 2.17 ± 0.49 ml (range, 1.0 -3.0 ml) and 6.79 ± 0.83 ml (range 5.0 - 9.0 ml), respectively, whereas VBEST was 4.69 ± 0.16 ml (range, 2.0 - 8.0 ml). Ees was 1.35 ± 0.51 cmH2O/ml (range, 0.26–2.38 cmH2O/ml). The estimated Pew at VBEST was 3.16 ± 2.19 cmH2O (range, 0 -7.97 cmH2O). Patients with a body mass index (BMI) ≥ 25 kg/m2 had a significantly lower VMAX (5.88 [5.25-6] vs. 7.25 [7-8] ml, p=0.006) and a significantly lower VBEST (3.69 [2.5-4.38] vs. 5.19 [4-6] ml, p = 0.036) than patients with a BMI < 25 kg/m2. Patients with positive end-expiratory pressure (PEEP) ≥10 cmH2O had a lower VMIN and VBEST than patients with PEEP < 10 cmH2O, P > 0.05. Patients in the supine position had a higher esophageal pressure than those in the prone position with the same balloon filling volume.Conclusions: Calibration of esophageal pressure to identify the best filling volume of esophageal balloon catheters is feasible. The esophageal pressure can be influenced by BMI, PEEP and position. It is necessary to titrate the optimal inflation volume again when the PEEP values or the positions change. Keywords: Esophageal pressure, Esophageal balloon catheter, Balloon filling volume, Mechanical ventilation, Calibration